WATER TREATMENT METHOD AND WATER TREATMENT APPARATUS - KITANAKA ATSUSHI; TAKAGI RYOTA (2007)
PROBLEM TO BE SOLVED: To provide a water treatment method for carrying out the reverse osmosis treatment of waste water, such as sewage, by a reverse osmosis membrane after membrane separation activated sludge treatment, and can inhibit fouling causing a clogging of a reverse osmosis membrane due to an organic matter and the like contained in treated water after the membrane separation activated sludge treatment. SOLUTION: In the water treatment method comprising the process for carrying out the activated sludge treatment of water to be treated in a biological treatment tank, the process for carrying out the membrane separation treatment of a mixed liquid of the water to be treated and activated sludge in the inside or outside of the biological treatment tank by using a microfiltration membrane, and the process for carrying out the reverse osmosis treatment of the water after the membrane separation treatment, the process for removing hydrophilic organic matter is installed after the process for carrying out the membrane separation treatment, and before the process for carrying out the reverse osmosis treatment. COPYRIGHT: (C)2007,JPO&INPIT